Rate of administration of tuberculosis preventive treatment to pediatric household contacts and influencing factors - Ridwan, Ivani; Sofiah, Fifi; Rismarini, Rismarini (Paediatrica Indonesiana, 2025)
Background Providing tuberculosis preventive treatment (TPT) to household contacts is an important measure for preventing disease transmission. Various child-, parent-, and healthcare-related factors influence TPT provision. Objective To determine the rate of pediatric TPT administration in household contacts of pulmonary TB patients and its influencing factors. Methods An observational analytical study was conducted from May-August 2024 at primary healthcare facilities in Palembang, Indonesia. We included children in household contact with bacteriologically-positive pulmonary TB patients confirmed by molecular rapid diagnostic test  who were registered for treatment in community health centers in Palembang that had a TB treatment program. Results Among 364 household contacts of 114 TB cases, only 3.3% received TPT. The majority of parents or guardians were <35 years of age, were biological parents of the included children, had sub-minimum wage incomes, demonstrated good understanding of TPT, and had completed at least secondary education. The majority of children were female, over 5 years of age, and well-nourished according to parent or caregiver subjective perception. At the participating community health centers, healthcare workers in charge of the TB treatment programs were mostly paramedical staff and had good TPT knowledge, and drug availability was adequate. Children with caregivers aged ≥35 years were 12 times more likely not to receive TPT (aOR=12,093; 95%CI 1,544 to 94,713; P=0.018). Caregiver role in the family, economic status, knowledge level, education, travel distance, child factors, and health facility factors showed no significant association with TPT provision. Conclusion The rate of TPT provision in Palembang is low, far below the national target of 50-90%. Guardian age of ≤35 years was the only factor significantly associated with TPT provision.